2008
DOI: 10.1080/01411920701491961
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the school in the decision to participate in learning post‐16

Abstract: The paper reports on work in progress for a Department for Education and Skills (DfES)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 9 publications
(14 reference statements)
2
27
0
Order By: Relevance
“…McDonough's work appears to suggest that the amount of guidance provision is a key factor. Other research, however, appears to suggest that guidance may play a potential role in challenging classed expectations; guidance counsellors are found to be especially important sources of college-related information for young people with no family traditions, or experience, of higher education who make a choice to pursue such a pathway (McDonough 1997;Carbrera and La Nasa 2000;Perna and Titus 2004;Foskett et al 2008). The extent to which the nature of school-based guidance reinforces or challenges 'taken for granted' assumptions about the progression to higher education has, however, rarely been examined.…”
Section: Schools and The Transition To Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…McDonough's work appears to suggest that the amount of guidance provision is a key factor. Other research, however, appears to suggest that guidance may play a potential role in challenging classed expectations; guidance counsellors are found to be especially important sources of college-related information for young people with no family traditions, or experience, of higher education who make a choice to pursue such a pathway (McDonough 1997;Carbrera and La Nasa 2000;Perna and Titus 2004;Foskett et al 2008). The extent to which the nature of school-based guidance reinforces or challenges 'taken for granted' assumptions about the progression to higher education has, however, rarely been examined.…”
Section: Schools and The Transition To Higher Educationmentioning
confidence: 99%
“…Guidance counsellors are especially important sources of college-related information where young people with no family traditions, or experience, of higher education make a choice to pursue such a pathway (McDonough 1997;Perna and Thomas 2004;Foskett et al 2008). However, like students in Fig Lane, they are frustrated by the lack of adequate guidance.…”
Section: Barrack Streetmentioning
confidence: 99%
“…Foskett et al (2008), for example, discuss how schools with high socio-economic status (SES) catchment areas tended to deliver careers guidance that encouraged traditional academic careers, whilst schools with low SES catchment areas had a much stronger commitment to vocational pathways. Research by the Slack, Hughes and Rout (2013) also found that students predicted to do well at GCSE were less likely to receive advice about vocational options, while those predicted to do less well were more likely to.…”
Section: Context and Backgroundmentioning
confidence: 99%
“…An Ofsted survey conducted in 2013 similarly found that beyond CIAG often not being well coordinated, vocational training and apprenticeships were rarely promoted effectively. Additionally, schools with sixth forms have been found to, at times, lack impartiality by encouraging young people to stay at the sixth form post-16, without informing them of other possible routes (Blenkinsop et al 2006;Foskett, Dyke, and Maringe 2008). These concerns have also been echoed by policy-makers, with the previous Chair of the Education Select Committee, Graham Stuart, raising concern about schools who, put their own interests ahead of that of their pupils, restrict access to other education providers and make the filling of their sixth form places more of a priority than their statutory duty to provide independent and impartial advice and guidance for pupils.…”
Section: Provision Does Not Meet Statutory Requirementsmentioning
confidence: 99%